Challenges and Difficulties of First-Year Students: A Case Study at Borneo Tarakan University - Tri Astuti Sugiyatmi; Ika Noviantari; Hendy Lesmana; Tanti Tri Lestary (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2026)
This study aims to explore both the academic and non-academic challenges encountered by first-year medical students. Students in health programs, especially medical programs, face significant academic and non-academic challenges during their first year. The transition from high school to university, including the possibility of living away from home, presents a unique challenge that demands strong adaptability. Additionally, analytical skills are important for managing the rigorous academic workload of the first year. The block-based learning system for medical students, which combines various activities such as lectures, tutorials, practicums, and medical skills across diverse topics within a limited timeframe, further increases the academic burden. Method: An exploratory case study was applied, and the unit of analysis was carried out at the Faculty of Medicine at Borneo Tarakan University (UBT), and the subjects included both academic and non-academic data from students. Qualitative data were collected using interviews and observations with students, while the informants were selected from the first and second semesters. Results: This study effectively identified the challenges and difficulties faced by first-year medical students. Non-academic challenges include adapting from high school to college, shifting from teacher-centered learning in high school to student-centered learning, and adjusting to living in a boarding house far from parents. The academic challenge involves entering medical school, where the academic workload is high, and the timeframe is shortened due to the implementation of a block-based curriculum. Conclusion: Students encounter numerous challenges and difficulties during their first year, and their ability or failure to adapt will influence their progress in subsequent years. Therefore, academic, psychological, and social support are essential.